2010
DOI: 10.1051/0004-6361/201014615
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the hot gas in low-mass protostars

Abstract: Aims. "Water In Star-forming regions with Herschel" (WISH) is a Herschel key programme aimed at understanding the physical and chemical structure of young stellar objects (YSOs) with a focus on water and related species. [O i] emission is seen in low-velocity gas, assumed to be related to the envelope, and is also seen shifted up to 170 km s −1 in both the red-and blue-shifted jets. Envelope models are constructed based on previous observational constraints. They indicate that passive heating of a spherical en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(26 citation statements)
references
References 20 publications
(28 reference statements)
2
23
1
Order By: Relevance
“…A.1a). This particular position has also been associated with a series of blueshifted water maser emissions (van Kempen et al 2009) and a bright spot of ion emission in the near-IR (Dionatos et al 2014). In Fig.…”
Section: Appendix A: Relations With Temperature/velocity Components Fmentioning
confidence: 79%
See 1 more Smart Citation
“…A.1a). This particular position has also been associated with a series of blueshifted water maser emissions (van Kempen et al 2009) and a bright spot of ion emission in the near-IR (Dionatos et al 2014). In Fig.…”
Section: Appendix A: Relations With Temperature/velocity Components Fmentioning
confidence: 79%
“…Since only a single transition of each molecule was observed, it is not possible to derive an excitation temperature from these data. The CO excitation temperature is set to 75 K, based on statistics of excitation temperatures for low-mass protostars (Yıldız et al 2015;van Kempen et al 2009) which show that the bulk of the low-J CO emission can be fitted with this value. Assessment of the excitation temperatures for other molecules is not straightforward.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The next step consists of detailed 2D modeling for each protostar. Such a model has already been developed and tested for the low-mass protostar HH46 (van Kempen et al 2010;Visser et al, in prep.). The model consists of three separate physical components: the molecular envelope heated by the accretion luminosity of the protostar, UVheating of the outflow cavity walls and shocks along the cavity walls (see Fig.…”
Section: Low-mass Ysosmentioning
confidence: 99%
“…van Kempen et al (2010a) and Visser et al (2012) explored the origin of the mid-J CO emission as arising from the UVheated gas along the outflow cavity walls (the photondominated region, PDR) and small-scale C-type shocks inside the walls. Furthermore, Visser et al (2012) suggested that the PDR contributes more to the FIR CO emission as the protostar evolves.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it may not be negligible because FUV observations toward classical T Tauri stars find that these stars emit UV photons at a few percent of the accretion luminosity (e.g., Herczeg et al 2002;Yang et al 2012). These UV photons can affect the physical and chemical properties of exposed gas within the outflow cavity and along the walls (van Kempen et al 2010a;Visser et al 2012;Lee et al 2014b, hereafter Paper I). In this regard, Yıldız et al (2012) used spectrally resolved observations of 13 CO J = 6-5, finding that the narrow emission lines (D < -v 2 km s 1 ) toward NGC 1333-IRAS 4A are consistent with emission from UV-heated outflow cavity walls, which encapsulate the broad outflow lines (D > -v 10 km s 1 ).…”
Section: Introductionmentioning
confidence: 99%